2012
DOI: 10.4254/wjh.v4.i3.50
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic encephalopathy: An approach to its multiple pathophysiological features

Abstract: Hepatic encephalopathy (HE) is a neuropsychiatric complex syndrome, ranging from subtle behavioral abnormalities to deep coma and death. Hepatic encephalopathy emerges as the major complication of acute or chronic liver failure. Multiplicity of factors are involved in its pathophysiology, such as central and neuromuscular neurotransmission disorder, alterations in sleep patterns and cognition, changes in energy metabolism leading to cell injury, an oxidative/nitrosative state and a neuroinflammatory condition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 181 publications
(174 reference statements)
0
35
0
4
Order By: Relevance
“…In animals experiments with the administration of an inhibitor of astrocytic GlnS the severity of edema was significantly decreased [27]. It is also supposed the active participation of glutamine in the mechanisms of oxidative and nitrosative stress, which are of great importance in the pathobiochemical cascade reactions in brain in conditions of hyperammonemia [15]. On the other hand, in studies carried out on rat model of portocaval anastomoses with additional administration of ammonium acetate, it is shown that when using methionine sulphoximine, an inhibitor of glutamine synthetase, the drug does not completely arrested cerebral edema, indicating that the osmotic properties of glutamine only partially explain the mechanisms of edema development in conditions of hyperammonemia [28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In animals experiments with the administration of an inhibitor of astrocytic GlnS the severity of edema was significantly decreased [27]. It is also supposed the active participation of glutamine in the mechanisms of oxidative and nitrosative stress, which are of great importance in the pathobiochemical cascade reactions in brain in conditions of hyperammonemia [15]. On the other hand, in studies carried out on rat model of portocaval anastomoses with additional administration of ammonium acetate, it is shown that when using methionine sulphoximine, an inhibitor of glutamine synthetase, the drug does not completely arrested cerebral edema, indicating that the osmotic properties of glutamine only partially explain the mechanisms of edema development in conditions of hyperammonemia [28].…”
Section: Introductionmentioning
confidence: 99%
“…Despite more than 200 years (since 1765, when Giovanni Battista Morgagni was the first to describe a case of liver cirrhosis with HE) studying of the problem and numerous attempts to formulate a common pathogenetic concept of HE, to date there is no holistic view on the factors of etiopathogenesis and accordingly there is no single approach to managing such patients [15]. Data on the morphogenesis of HE in the current literature are of limited character and are presented in form of single studies of predominantly experimental character.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an uncommon, but not rare, condition with approximately 2,000 cases annually in the United States and a mortality rate ranging from 50% to 90%, despite intensive care therapy 1,2 . Cerebral edema leading to intracranial hypertension complicates approximately 50% to 80% of patients with severe FHF (grade III or IV coma), in whom it is the leading cause of death 2,3,4 . Brain edema in FHF patients is a relatively recent concept.…”
mentioning
confidence: 99%